Distress in long‐term head and neck cancer carers: a qualitative study of carers' perspectives. Issue 15 (10th May 2016) - Balfe, Myles; Maguire, Rebecca; Hanly, Paul; Butow, Phyllis; O'Sullivan, Eleanor; Timmons, Aileen; Gooberman‐Hill, Rachael; Sharp, Linda
Abstract : Aims and objectives: To identify and describe the triggers of emotional distress among long‐term caregivers (more than 1 year postdiagnosis) of people with head and neck cancer. Background: Limited research has been conducted on the factors that cause head and neck cancer caregivers to become distressed. Design: Qualitative cross‐sectional. Methods: In‐depth semi‐structured interviews. Interviews were conducted via telephone. The study setting was the Republic of Ireland. Results: Interviews were conducted with 31 long‐term caregivers (mean time since diagnosis 5·7 years, SD 2·9 years). Head and neck cancer caregivers experienced significant distress. Six key triggers of emotional distress were identified: understandings and fears of illness, lifestyle restrictions and competing demands, facial disfigurement, financial problems, comorbid health problems and witnessing suffering. Cutting across all of these individual causes of distress was a strong feeling of loss caused by head and neck cancer. Conclusions: Some head and neck cancer caregivers became considerably distressed by their caring role. Although distress appears to decline with time for many caregivers, some continue to be distressed for years following the patient's diagnosis. It would be useful for future research to explicitly investigate caregivers' experiences of loss. Relevance to clinical practice: Health professionals may be able to reduce distress in this group if they can help caregivers to access resources that can be used to buffer financial problems. Health professionals may also be able to reduce distress if they can work with caregivers to help them to obtain something of personal value or significance from their experience of loss and suffering.